Fatores não biológicos associados à cárie dentária: um estudo qualitativo em odontopediatria - Canalli, Cláudia da Silva Emílio (2010)
Dental caries is an infectious, transmissible disease resulting from the complex interaction of multiple factors. Accordingly, its approach should go beyond the limits of the biological field. Those aspects justify the importance of this study which covers non-biological factors involved in the pathogenesis of caries disease in children aged up to seventy-one months who assiduously attend the Baby-Clinic program of Unigranrio/RJ, Brazil. The purposes of the research were: to identify and analyze the non-biological factors that contribute toward the development of dental caries in that group and to provide data that would contribute toward achieving a broader view of the phenomenon of dental caries in children. The data collection for this qualitative study consisted of an individual, semi-structured interview guided by a schedule. The analysis procedure was based on the Categorical Content Analysis. The research followed ethical procedures guided by Resolution 196/96. The participants were sixteen carers of children who, although assiduously attending the Baby-Clinic program of UNIGRANRIO/RJ, Brazil, developed dental caries. The parental relationship of the children comprised thirteen mothers, two grandmothers and one father. The grouping of the topics gave rise to three analytical categories entitled: 1 – Carer perception and knowledge of the phenomenon of dental caries; 2- Influence of the construction of habits and the phenomenon of dental caries; 3 – Other factors associated with dental caries. The results of the data analysis suggest the coexistence of various non-biological factors converging on the phenomenon of dental caries, namely: lack of/deficient oral hygiene, carer stress, family destructuring, low level of oral health knowledge, inadequate feeding habits, and lack of collaboration from the various family members with the person responsible for taking care of the child’s oral health. The interaction of these factors indicates the need for the dental surgeon to look beyond the tooth cavity at the patient’s life context ensuring a humanized, global and contextualized approach.